(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the acceptance rate of COVID-19 vaccination and related factors among pregnant women attending Da Nang Hospital for Women and Children in 2022. Method: A cross-sectional study was conducted from February 2022 to July 2022 on 535 pregnant women at the General Examination - Emergency Department of Da Nang Hospital for Women and Children. Pregnant women were interviewed using a pre-designed structured questionnaire. All analysis procedures were performed using Stata 16.0 software. Results: Among the 535 pregnant women participating in the study, 33.5% accepted the COVID-19 vaccination. Factors associated with COVID-19 vaccination acceptance included age group, educational level, occupation, trimester of pregnancy, and interval since the last childbirth. Conclusion: The acceptance rate of vaccination among pregnant women remains quite low. Communication programmes emphasising the vaccine’s safety are necessary to encourage pregnant women to get vaccinated against COVID-19.